Agriculture: Toward the year 2000: Major results of the FAO-report - Heinrich Loesch (Intereconomics, 1979)
When the World Food Conference of 1974 demanded the eradication of world hunger within the brief time span of ten years, experts and laymen alike were surprised. The target seemed too ambitious, and it can be safely expected that it will not be achieved. A study has now been submitted by FAO to its 20th Plenary Conference session which—without proposing a new target date—attempts to prove the feasibility of greatly reducing world hunger before the advent of the 21st century.
Keywords: 330; Nutrition